Sociological genealogy of a non-teleological concept of evolution - Beriain, Josetxo; Gil-Gimeno, Javier; Capdequí, Celso Sánchez (Frontiers in Sociology, 2024)
The aim of this article is to carry out a sociological-conceptual genealogy of the evolutionist perspective (non-teleological) of approaching social reality. While during the first phases of modernity, a teleological and progressive conception of evolution was imposed, clearly manifested in the proposals of Auguste Comte or Herbert Spencer, in the last decades important bifurcations, processes, and developments have emerged that question the linearity and the finalist character of these positions. We consider that these approaches are closer to the nature of change and social phenomena, so it seems important to us to analyze some of the most outstanding contributions—in the form of sociological genealogy, as we have already mentioned—that have developed this perspective. In order to carry out our task, we have organized four sections: In the first, we make a critique of the sociological evolutionism represented by Comte, Spencer, and Parsons, focusing on the limits of their proposals and the blind spots associated with them. Second, we will analyze the anti-teleological cognitive approaches of Donald and the importance they attach to cultural transmission as a key element for understanding the evolution of both cognition and human societies. In a third moment, we will analyze the coexistence in Weber’s work between the dynamics of ‘disenchantment’ and ‘re-enchantment’ of the world in modern societies, understood as the two sides of the same coin that are in constant dynamic tension and that break with the evolutionary vision that goes from magic through religion to science, or from belief to knowledge. In a fourth moment, we analyze the relevance of approaches focused on what we have called ‘multiple evolutions’ (plural) that collide with each other—the conflicting simultaneity of the non-simultaneous—of their rhythms and directions, inspired by the works of Knöbl, Koselleck, Luhmann, Rosa, Eisenstadt, Abbott, and Zerubavel, which pave the way for the construction of a non-teleological approach to evolution.